The phenomenon of violence in the school environment: reasons, means of prevention and treatment: A field study on a sample of high school students, Lieutenant Ibrahim bin Othman - Bir El Ater - Tebessa - Mebarkia, Oussama; Rahoui Abassia, Belhocine (Journal of Human Sciences, 2022)
The phenomenon of violence is one of the most widespread and aggravating social phenomena and one of the main major issues that arouse the interest of researchers in the social sciences, because of its negative effects on the individual and society in all its institutions, especially the school, this space, which has become today a playground for riots and violence. . The study aimed to search for the causes of school violence and ways to prevent it, for this a form was prepared consisting of five main axes, the questions of which varied between open and closed, and were distributed to a sample of 40 schoolchildren who riot inside the secondary school. Consequently, the study reached the phenomenon of school violence, which is controlled by several subjective reasons related to the personality of the student, family and school ...